2022
DOI: 10.1002/mus.27731
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid characteristics of patients treated with intrathecal nusinersen for spinal muscular atrophy

Abstract: Introduction/Aims There is limited information on the potential effects of repeated intrathecal antisense oligonucleotide drug delivery on cerebrospinal fluid (CSF) biochemical and blood cell profiles. This study aimed to examine longitudinal changes in the biochemical components (glucose, protein) and blood cell counts in the CSF of spinal muscular atrophy (SMA) patients treated with intrathecal nusinersen. Methods We collected and analyzed clinical and CSF parameters (cell count, protein, glucose, culture) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Overall, 23 studies on SMA treatment included SMN2 copy number ( 67–89 ), but only 11 of these studies examined treatment effects in patients with three SMN2 copies ( Supplementary Table S6 ) ( 68 , 69 , 71 , 74 , 79 , 80 , 83 , 85 , 87–89 ). The 12 excluded studies did not allow analysis of treatment effects in patients with three SMN2 copies ( Supplementary Table S7 ) ( 67 , 70 , 71 , 73 , 75–78 , 81 , 82 , 84 , 86 ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 23 studies on SMA treatment included SMN2 copy number ( 67–89 ), but only 11 of these studies examined treatment effects in patients with three SMN2 copies ( Supplementary Table S6 ) ( 68 , 69 , 71 , 74 , 79 , 80 , 83 , 85 , 87–89 ). The 12 excluded studies did not allow analysis of treatment effects in patients with three SMN2 copies ( Supplementary Table S7 ) ( 67 , 70 , 71 , 73 , 75–78 , 81 , 82 , 84 , 86 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies looking at routine CSF parameters of patients with SMA receiving nusinersen have consistently shown a mild increase in CSF protein and CSF/serum quotients of albumin without further signs of inflammation. This has been discussed to be the result of either nusinersen treatment or repeated lumbar punctures [11][12][13]. In rats, using multimodal imaging and radioactively and fluorescently labelled ASO, it was shown that after intrathecal injection they strongly associate with the meninges and are subsequently transported to lymph nodes [14].…”
Section: Discussionmentioning
confidence: 99%
“…[ [180][181][182] tion factors [95][96][97][98][99], and long non-coding RNAs [100][101][102][103]; biomolecular factors such as SMN protein [18,39,48,57,81,[104][105][106], neurofilament (NF) [78,[107][108][109][110][111][112][113][114][115][116][117][118], tau protein [112,[119][120][121], and muscle damage indicators [122][123][124]; muscle imaging parameters including magnetic resonance imaging (MRI) [122][123][124] and electrical impedance myography (EIM) [75,[125][126][127]; and electrophysiological parameters including compound muscle action potential (CMAP) [128]…”
Section: Imaging Candidatesmentioning
confidence: 99%